The dynamics between entrepreneurship, environment and education - Fayolle, Alain; Kyrö, Paula, 1953-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2008)
This book introduces the expanding European dialogue between entrepreneurship, environment and education. It considers the shape, dimensions and horizon of this multidisciplinary landscape in entrepreneurship research. The striking differences and contradictions in entrepreneurial activities, readiness and innovativeness within European countries and the proactive attitude and activities of European competitors impose a demand for a better understanding of the complex dynamics.
pt. 1. The dynamics between entrepreneurship and environment -- pt. 2. The dynamics between entrepreneurship and education -- pt. 3. The dynamics between entrepreneurship and small businesses.
Includes bibliographical references and index.
Keywords: Entrepreneurship; Entrepreneurship -- Study and teaching; Economic development -- Environmental aspects; Electronic books